Longitudinal impact of bladder cancer diagnosis on common psychiatric disorders. (12th November 2021) - Cooke, Ian J.; Patil, Dattatraya; Bobrek, Katherine; Narayan, Vikram; Master, Viraj; Rapaport, Mark; Filson, Christopher P.; Joshi, Shreyas S.
Abstract: Background: The presence of psychiatric disorders in patients with cancer is associated with increased morbidity and poorer outcomes. We sought to determine the impact of a new bladder cancer diagnosis on the incidence of depression and anxiety. Methods: We used a database of billing claims (MarketScan®) to identify patients newly diagnosed with bladder cancer between 2009 and 2018. Patients with preexisting psychiatric disorders or use of anxiolytics/antidepressants were excluded. We matched cases to patients without a bladder cancer or psychiatric diagnosis. Our primary outcome was a new diagnosis of depression, anxiety, or use of anxiolytics/antidepressants. Other exposures of interest included gender and treatment received. We used multivariable regression to estimate odds ratios for these exposures. Results: We identified 65, 846 cases with a new diagnosis of bladder cancer (31, 367 privately insured; 34, 479 Medicare‐eligible). Compared to controls, bladder cancer patients were more likely to develop new‐onset depression/anxiety at 6 months (privately insured: 6.9% vs. 3.4%, p < 0.001; Medicare‐eligible: 5.7% vs. 3.4%, p < 0.001) and 36 months (privately insured: 19.2% vs. 13.5%, p < 0.001; Medicare‐eligible: 19.3% vs. 16.0%, p < 0.001). Women (vs. men, privately insured: OR 1.65, 95%CI 1.53–1.78; Medicare‐eligible: OR 1.63, 95%CI 1.50–1.76) and those receiving cystectomy and chemotherapy (vs. no treatment, privately insured: OR 4.94, 95%CI 4.13–5.90; Medicare‐eligible: OR 2.35, 95%CI 1.88–2.94) were more likely to develop significant depression/anxiety. Conclusion: A new diagnosis of bladder cancer was associated with increased burden of significant depression/anxiety compared with matched controls. Women and patients receiving more radical treatments had higher rates of depression and anxiety. Abstract : Using a large, nationally representative sample, we found that a new diagnosis of bladder cancer was associated with increased burden of mental health diagnoses and medication utilization compared with matched controls. Female patients and those receiving more radical treatments for bladder cancer had higher rates of major depressive disorder, generalized anxiety disorder, and psychiatric medication utilization.